The Business of Piracy in Somalia - Anja Shortland
This article argues that it will be difficult, if not impossible, to control Somali piracy for four reasons. First, Somali piracy is a land-based problem and naval control mechanisms are not changing the incentives for pirates. Second, improving Somalia's anarchic political situation will not necessarily stop piracy. Our analysis demonstrates that piracy is a business which improves with a more stable operating environment. Third, piracy is organized criminal activity, and like other organized crime groups will be difficult to control, especially if it becomes embedded in state structures. Finally, we argue that few of the relevant players have any real incentives to alter their behaviour.Piracy, Somalia, Law Enforcement, Organised Crime, EU Atalanta